Evaluation of Biodegradable Fixation System for Mandibular Angulus Fracture by Using Finite Element Method - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2016)
To date many fixation techniques of mandibular angle fractures have been introduced. There exist much research on the stability of plate and screws systems used in Champy technique in fixation of mandibular fractures. However the need of a second surgery for the removal of these plates and screws, and well known disadvantages of metallic fixations have led to the development of resorbable materials. It is thought that in order to achieve a safe and effective post-operative stability, the use of resorbable plates and screws is preferred for fixation. In this study, fixation evaluation of biodegradable plates which have been commonly used in recent years, was investigated using finite element method. 3D model required to perform the finite element analysis was obtained from CT scanning images using reverse engineering methods and material properties of mandible were obtained by Hounsfield Unit method. Biodegradable fixation systems were applied to this model and FEA was performed. It is concluded that biodegradable plate screw system used in the treatment of mandibular angle fractures shows a sufficient stability under masticatory forces.
Keywords: ANGLE